Teacher Obstacles in Providing Student Attitude Assessment in the Learning Process Based on the 2013 Curriculum - Didin Nuriana (Madrosatuna: Journal of Islamic Elementary School, 2018)
This study entitled "Teacher Constraints in Providing Assessment of Student Attitudes in Learning Process Based on 2013 Curriculum in Subang Aliyah Madrasas". The formulation of the problem in this study is how the teacher in giving an assessment of student attitudes in the learning process based on the 2013 curriculum at the Subang Aliyah Madrasah? What is the difficulty of the teacher in giving an assessment of student attitudes in the learning process based on the 2013 curriculum at the Subang Aliyah Madrasah? How are the efforts made by the teacher in overcoming the difficulties of giving a value to the attitudes of students in the learning process based on the 2013 curriculum in the Aliyah Subang Madrasah? The conclusions of the results of this study indicate that the teacher provides an assessment of the attitudes of students in the learning process based on the 2013 curriculum at Subang Aliyah Madrasah by observing or making observations directly on student attitudes during the learning process. The difficulty of the teacher in giving an assessment of the attitudes of students in the learning process based on the 2013 curriculum in Subang Aliyah Madrasah is the limited time, the large number of students in one class and the difficulty of directing students to instill good attitudes according to the learning objectives. The efforts made by the teacher in overcoming the difficulties of giving scores on students' attitudes in the learning process based on the 2013 curriculum at Aliyah Subang Madrasah are by holding discussions with parents of students, coordinating with other teachers and also asking other students to get detailed information.